IoT based Ambulance Prototype for Innovative Traffic Congestion Control System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Traffic congestion is a major problem in cities of developing Countries like India. Growth in urbanpopulation and the middle-class segment contribute significantly to the rising number of vehicles inthe cities. Congestion on roads eventually results in slow moving traffic, which increases the time oftravel, thus stands-out as one of the major issues in metropolitan cities. This paper presents anintelligent traffic control system to pass emergency vehicles smoothly. Each individual vehicle isequipped with special radio frequency device. We use radio frequency (Rf)transmitter (Tx) andreceiver (Rx) modules at ambulance and traffic signal respectively. It monitors vehicles that passes ona path during a specified duration. It also determines the network congestion, and hence the greenlight duration for that path. If the ambulance passes through the path it switches on the green lightuntil it passes the signal area.